Menstrual health in indigenous Tseltal women from Pathuitz and Mequejá, in Chilón, Chiapas, Mexico - Vega-Barrero, Adriana Marcela (2025)
Introduction: In Mexico, menstruation is not even listed in official statistics, perpetuating the taboo, fear and ignorance on the subject, even more so in indigenous populations living in extreme poverty. Our objective was to analyze the menstrual experiences of young and adult women of the Tseltal indigenous communities of Pathuitz and Mequejá in Chilón, Chiapas, considering the definition of Menstrual Health of the “The Global Menstrual Collective's Terminology Action Group” under the focus of gender and feminist health. Methodology: Qualitative methodology promoting the co-research with the association “Asociación Yip Yatel Tseltal Ansetic A.C.” defending the participation of indigenous women as collaborators and researchers. We analyze the menstrual experience of 17 Tseltal women, and the perception of 4 men through semi-structured interviews and activist participatory observation and from situated knowledge. Results: Challenges for Tseltal women in living a healthy menstruation: a) precarious information about menstruation and experiences of fear and shame, b) economic difficulty to acquire menstrual management products, c) restriction of their activities, d) pain, disorders and lack of awareness of the menstrual cycle, e) limited access to medical services. We also analyze the water services, sanitation and hygiene systems at home and schools, and the acceptance of reusable cloth sanitary pads as an option adapted to the context. Conclusion: women have opened up about the topic for the first time, generating interest to know about menstruation, the body and menstrual cycle. They have successfully adopted the use of reusable cloth sanitary pads, given they save money, feel comfortable and are able to leave the house.